Analisis Struktur, Perilaku dan Kinerja Pemasaran Kentang (Solanum Tuberosum) di Nagori Hutaraja Kecamatan Purba, Kabupaten Simalungun - Damanik, Desy Wulan Sary; Lubis, Mitra Musika; Safitri, Sri Ariani (AGRISAINS: Jurnal Ilmiah Magister Agribisnis, 2025)
Potatoes are used as an alternative food ingredient to meet the food and nutritional needs of the community. Having high economic value, potatoes can be processed into various forms of processed food products that can be used as safe substitute food ingredients (Cahyadi et.al 2020). The purpose of this study was to determine the structure, behavior, and marketing performance of potatoes in Nagori Hutaraja. The research method used was qualitative descriptive. Sampling was carried out purposively. The samples in the study were potato farmers, collectors, wholesalers, retailers, and consumers. The data collected in this study were primary data and secondary data. the total number of population which is the result of qualitative or quantitative measurements or calculations regarding the characteristics whose properties are to be studied. The population in this study is all potato farmers in Nagori Hutaraja. The analysis method used in this study was analysis, market structure (market share, market concentration, and barriers to entry and exit of the market), market behavior analysis, and market performance analysis (farmer share and marketing margin)